The Analysis of Students' Psychological Problems and Its Solutions in Speaking English at One of the Junior High Schools in Aru Islands - Imelda Tahalele; Felicia Miranda Lekatompessy; Wensy Steva Nussy (MATAI: International Journal of Language Education, 2023)
and their solutions in speaking English. The research design of this study was a mixed method with an explanatory sequential design approach. The population of this study was second-grade students, and its sample was two classes consisting of 60 students and 3 English teachers who taught them. The instruments used in this study were questionnaires and interviews. The quantitative data were analyzed using the formula from Sugiyono (2005) f/n x 100%, while the qualitative data was analyzed using the technique by Miles and Huberman (1992:16) data reduction, data display, and conclusion drawing/verifying. The results of this study indicate that students still have problems speaking English, especially psychological problems such as fear of making mistakes, lack of self-confidence, lack of motivation, and anxiety. Therefore, based on the problems above, there are several solutions provided by teachers and students to overcome these problems.